2008
DOI: 10.3892/ijo.32.2.289
|View full text |Cite
|
Sign up to set email alerts
|

The HMGA proteins: A myriad of functions (Review)

Abstract: Abstract. The 'high mobility group' HMGA protein family consists of four members: HMGA1a, HMGA1b and HMGA1c, which result from translation of alternative spliced forms of one gene and HMGA2, which is encoded for by another gene. HMGA proteins are characterized by three DNA-binding domains, called AT-hooks, and an acidic carboxy-terminal tail. HMGA proteins are architectural transcription factors that both positively and negatively regulate the transcription of a variety of genes. They do not display direct tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
248
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(269 citation statements)
references
References 113 publications
10
248
1
10
Order By: Relevance
“…Rearrangement and resultant overexpression of HMGA2 has been implicated in a variety of human neoplasms. 30 Whereas our data confirmed that all four cases with gains of HMGA2 also expressed the encoded protein, four additional cases without the gain expressed HMGA2 protein as well, indicating alternative mechanisms of upregulating this protein, such as genetic rearrangement. Interestingly, HMGA2 rearrangement or amplification has been implicated in some endometrial polyps.…”
Section: Discussionsupporting
confidence: 59%
“…Rearrangement and resultant overexpression of HMGA2 has been implicated in a variety of human neoplasms. 30 Whereas our data confirmed that all four cases with gains of HMGA2 also expressed the encoded protein, four additional cases without the gain expressed HMGA2 protein as well, indicating alternative mechanisms of upregulating this protein, such as genetic rearrangement. Interestingly, HMGA2 rearrangement or amplification has been implicated in some endometrial polyps.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, deletions of 7q22, 22q, and 1p frequently co-occurred with other genetic changes and had no major influence on the clustering, suggesting that these changes are involved in tumor progression rather than initiation. Leiomyomas with HMGA1 or HMGA2 alterations displayed similar global expression signatures, supporting the idea that these structurally and evolutionarily related transcription factors have similar functions in tumorigenesis (32). The majority of quadruplenegative leiomyomas clustered into several unique branches, indicating the presence of multiple rare and possibly novel subtypes.…”
Section: Discussionsupporting
confidence: 52%
“…HMGA2 encodes a protein belonging to the non-histone high mobility group protein family. The protein influences an array of cellular processes through regulation of gene transcription [38]. In addition to oncocytic lipoadenoma, HMGA2 gene rearrangements have also been recognized in a number of other neoplasms, including soft tissue lipomas and a subset of salivary gland pleomorphic adenomas [39,40].…”
Section: Discussionmentioning
confidence: 99%